Digital_Humanities - Burdick, Anne (The MIT Press, 2012)
A visionary report on the revitalization of the liberal arts tradition in the electronically inflected, design-driven, multimedia language of the twenty-first century. Digital_Humanities is a compact, game-changing report on the state of contemporary knowledge production. Answering the question "Whatis digital humanities?," it provides an in-depth examination of an emerging field. This collaboratively authored and visually compelling volume explores methodologies and techniques unfamiliar to traditional modes of humanistic inquiry-including geospatial analysis, data mining, corpus linguistics, visualization, and simulation-to show their relevance for contemporary culture. Written by five leading practitioner-theorists whose varied backgrounds embody the intellectual and creative diversity of the field, Digital_Humanities is a vision statement for the future, an invitation to engage, and a critical tool for understanding the shape of new scholarship.